1986
DOI: 10.1016/0039-6028(86)90357-2
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ru subcarbonyls by reaction of CO with stepped Ru single crystal surfaces

Abstract: The interaction of CD with Ru field emitter surfaces has been studied by pulsed field desorption mass spectrometry (PFDMS) at a pressure of 1.3X10 4 Pa CO and temperatures r, = 32X K and r, = 458 K. Probing the stepped region in the vicinity of the (001) pole of the Ru field emitter, various ionic species have been detected, including singly and doubly charged specks Ru(CO):'+ (.r = I-4). The intensities of the Ru suhcarbonyl species ax well as their relative abundances depend on the field strength, the repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The present PFDMS results prove such Co-subcarbonyls to be formed indeed. Previous studies of carbonyl formation on metals like Ni, Ru or Rh [5,7,16,17] have demonstrated carbonyls to be mobile and likely involved in morphological shape transformations. Future studies by PFDMS will address the question for a possible Co(CO) x,ad mobility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present PFDMS results prove such Co-subcarbonyls to be formed indeed. Previous studies of carbonyl formation on metals like Ni, Ru or Rh [5,7,16,17] have demonstrated carbonyls to be mobile and likely involved in morphological shape transformations. Future studies by PFDMS will address the question for a possible Co(CO) x,ad mobility.…”
Section: Resultsmentioning
confidence: 99%
“…With this background, it appears challenging to examine whether proven concepts of metal-organic chemistry can be applied to metal surfaces as well. For example, the formation of adsorbed metal-subcarbonyls was reported for a number of metals including Ni [5], Co [6] and Ru [7] but despite earlier claims [8] the possible role of such species in the hydrocarbon chain growth mechanism remains unknown at present.…”
Section: Introductionmentioning
confidence: 96%
“…It was previously demonstrated see, for example, Ref. [8] that a systematic variation of the pulse field strength can reveal whether or not diffusion is in operation. Usually, high field strengths can suppress the influence of long-range diffusion from the shank of the tip into the crystal apex region.…”
Section: Resultsmentioning
confidence: 97%
“…Probably the most detailed kinetic information on surface reactions available at present is that of carbonyl formation on transition metals such as Ni [104], Co [105], Ru [106], Pd [107] and Rh [100]. Some of them have since been overcome, for example, by using synchrotron radiation, but others are inherent to the method.…”
Section: B Kinetics and Mechanisms As Measured By Local Probe Methodsmentioning
confidence: 99%